COLLOIDAL DISPERSION GELS (CDG) TO IMPROVE VOLUMETRIC SWEEP EFFICIENCY IN WATERFLOODING PROCESSES - Rubén-Hernán Castro-García; Gustavo-Adolfo Maya-Toro; Jorge-Eduardo Sandoval-Muñoz; Lia-Margarita Cohen-Paternina (CT&F Ciencia, Tecnología & Futuro, 2013)
ABSTRACT A viable option for the sustainability of hydrocarbon supply in the short and medium term is increasing the expected ultimate oil recovery factor through Enhanced Oil Recovery processes (EOR). The purpose of this paper is to describe a methodology to evaluate EOR technologies developed at the Instituto Colombiano del Petróleo (ICP) of ECOPETROL S.A. in 2012. The methodology includes theoretical evaluation, design (geological analysis, engineering analysis, laboratory static and dynamic tests and numerical simulation, among others), field implementation and surveillance of Colloidal Dispersion Gels (CDG) injection. CDG is an EOR method that consists in the co-injection of high molecular weight polymer and a crosslinker, to generate microgels in the reservoir. This technology has become an alternative to polymer flooding. This paper describes a field application in Dina Cretáceos Field (Dina) supported by the proposed methodology, which corresponds to the first chemical enhanced oil recovery pilot implemented in Colombia by ECOPETROL S.A. Results of this study show an increase in volumetric sweep efficiency due the improvement of the mobility ratio, increasing in oil production and decreasing in water production. Based on the results of this pilot, which started in June 2011, the feasibility of expanding the use of CDG technology in Dina and others fields of Colombia is being assessed at present.